2019
DOI: 10.1055/s-0039-3400672
|View full text |Cite
|
Sign up to set email alerts
|

Modified Capanna’s Technique (Vascularized Free Fibula Combined with Allograft) as a Single-Stage Procedure in Post-traumatic Long-Segment Defects of the Lower End of the Femur: Outcome Analysis of a Series of 19 Patients with an Average Gap of 14 cm

Abstract: Objectives Salvage and reconstruction of posttraumatic defects of the long bone are complex due to the multiple procedures involved and increased chances of poor outcomes. We present the outcomes of the modified Capanna’s technique—a reliable single-stage procedure of combining allograft and free vascularized fibular graft—in treating large posttraumatic bone defects in the distal third of the femur. Study Design This is a retrospective analysis. Materials and Methods Between April 2012 and September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The mean time to union in the biological reconstruction of extended bone defects varies and depends on the technique used, ranging from four to over twelve months, and full weight-bearing rarely occurs before four to six months [ 12 , 39 , 40 , 41 , 42 ]. With our method, the osteoinductive role played by the induced membrane can exert a positive impact on the bone healing of the graft, with fast allograft and fibula union, early weight-bearing, and a satisfactory functional score.…”
Section: Discussionmentioning
confidence: 99%
“…The mean time to union in the biological reconstruction of extended bone defects varies and depends on the technique used, ranging from four to over twelve months, and full weight-bearing rarely occurs before four to six months [ 12 , 39 , 40 , 41 , 42 ]. With our method, the osteoinductive role played by the induced membrane can exert a positive impact on the bone healing of the graft, with fast allograft and fibula union, early weight-bearing, and a satisfactory functional score.…”
Section: Discussionmentioning
confidence: 99%
“…Here, vascularised fibula with an allograft has been used. 23 The authors have explained that the allograft would help in providing the strength until the fibula attains the size of the recipient bone. If we do not have an option of using an allograft, use of doble barrel fibula is recommended which would add strength to the reconstructed bone.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, when a double-barrel graft is utilised, the length of the defect that can be reconstructed becomes significantly lower. So, it would be a major challenge to reconstruct defects of more than 12 cm [13] , [14] , [15] , [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Jayaramaraju D et al had reported the result of modified capanna's technique using vascularized free fibular graft combined with allograft for post-traumatic long-segment defects of the lower end of the femur [13] . They reported that the bony union was achieved at mean of 6.6 months (range: 5-9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation